Employment of Mathematical Statistics in Civil Engineering and Its Role in Statistical Quality Control in Construction Projects - Al-Mamoori, Sora (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Mathematical statistics plays an integral role in the current state of civil engineering applications. This paper discusses the application of statistical approaches in the improvement of planning and execution processes in the context of construction activities. Practical applications include cost analysis and risk assessment. By using an analytical and inductive approach based upon existing research studies published in reputable sources, the paper illustrates the author’s point that the combination of statistical approaches improves the quality of output and leads to the reduction of variations regarding the analysis of civil engineering applications. This paper represents the author’s personal research analysis and findings based upon the verification of established statistical principles.